ANALYSIS OF TIME AND COST OF IMPLEMENTING THE CONSTRUCTION WORK OF BUILDING A UNIT OF NEW SCHOOL SMP N 47 PADANG BASED ON CHANGES IN BUILDING DESIGN - Helny Lalan; Dika Prasetyo; Dian Wahyoni DF; Dyla Midya Octavia (Ikatan Dosen Menulis, 2024)
The occurrence of changes in time and costs due to design changes and the addition of new work items affect the time and cost of implementing construction work. The addition of work items was also found in the construction of building A of the new school unit of SMPN 47 Padang. This is the impetus for conducting a time and cost analysis due to changes in building design and analyzing the index value of time and cost performance using the case study method and qualitative descriptive analysis. In the initial stage, identification of additional work items was carried out, then continued with an analysis of the time and cost using the Earned Value Analysis method. The results of data processing obtained the addition of new work items such as the board of directors, tree removal work, additional floors in buildings A and B so that they had an impact on the time and cost of implementation with an increase of 9.49%. Using the Earned value method, the SPI value was obtained with an average value of 0.798 and the CPI with an average value of 0.595. There was an additional implementation time of 25 calendar days and an additional implementation cost of Rp 1,016,937,031.14, - or an increase of 9.46%. The value and for SPI with an average value of 0.798 (<1) which indicates that the project is experiencing delays from the planned schedule, for CPI with an average value of 0.595 (<1) which indicates that the project's costs are greater than the budget.